2020
DOI: 10.1016/j.envint.2020.106108
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating consumer exposure to disinfecting chemicals against coronavirus disease 2019 (COVID-19) and associated health risks

Abstract: Highlights Exposure to disinfecting chemicals is highly dependent on physicochemical property. Children are at elevated exposure due to more mouthing-mediated ingestion. Some disinfecting chemicals may pose health risks for certain modeled individuals. Estimated risks differ greatly between the uses of in vivo and in vitro toxicity endpoints.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
94
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(95 citation statements)
references
References 53 publications
1
94
0
Order By: Relevance
“…Mandatory lifestyle changes, such as having to work or study at home coupled with fewer on average contacts might have also affected mental health outcomes, while staying more at home (increasing exposures to indoor air), or using more cleaning/disinfection products might have led to increased chemical exposures e.g. to disinfection by-products ( Kim et al, 2020 , Li et al, 2020 ). Upon school closures, education for many moved to online platforms, thereby adversely impacting learning opportunities for students with limited access to such technologies.…”
Section: Discussionmentioning
confidence: 99%
“…Mandatory lifestyle changes, such as having to work or study at home coupled with fewer on average contacts might have also affected mental health outcomes, while staying more at home (increasing exposures to indoor air), or using more cleaning/disinfection products might have led to increased chemical exposures e.g. to disinfection by-products ( Kim et al, 2020 , Li et al, 2020 ). Upon school closures, education for many moved to online platforms, thereby adversely impacting learning opportunities for students with limited access to such technologies.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, due to the COVID-19 pandemic, the use of biocides including disinfectants has increased significantly and accordingly, it is predicted that the exposure of disinfecting chemicals to the general population has also increased [ 25 , 26 ]. Since the use of disinfectants is a necessary for COVD-19 prevention, safety issues became more and more important.…”
Section: Discussionmentioning
confidence: 99%
“…Disinfectant use for cleaning both hands and surfaces has grown during the pandemic (17). Previous studies have shown pandemic related increases in concentrations of quaternary ammonium disinfectants in household dust (18), and higher risk of health effects due to increased exposure (19). Levels of two quaternary ammonium disinfectant chemicals increased in sludge during the overall study period (weekly samples, Figure 1d, Table S8).…”
mentioning
confidence: 87%